Symptomatic zinc deficiency in a breast-fed preterm infant. Issue 7 (July 1980) - Aggett, P J; Atherton, D J; More, J; Davey, J; Delves, H T; Harries, J T
Abstract : A 2-month-old preterm boy who developed symptomatic zinc deficiency while being exclusively breast fed is described. Oral zinc supplements induced a complete remission but mucosal 65Zn uptake studies and metabolic balances conducted before and after withdrawal of the supplements excluded the diagnosis of acrodermatitis enteropathica. By age 12 months the boy was well and no longer required zinc supplements. Other possible causes of this patient's symptomatic zinc deficiency are discussed and these should be considered in the immediate and long-term management of preterm infants.